Culture in Glucose-Depleted Medium Supplemented with Fatty Acid and 3,3′,5-Triiodo-l-Thyronine Facilitates Purification and Maturation of Human Pluripotent Stem Cell-Derived Cardiomyocytes - Lin, Bin; Lin, Xianming; Stachel, Maxine; Wang, Elisha; Luo, Yumei; Lader, Joshua; Sun, Xiaofang; Delmar, Mario; Bu, Lei (Frontiers in Endocrinology, 2017)
With recent advances in stem cell technology, it is becoming efficient to differentiate human pluripotent stem cells (hPSC) into cardiomyocytes which can subsequently be used for myriad purposes, ranging from interrogating mechanisms of cardiovascular disease, developing novel cellular therapeutic approaches, as well as assessing the cardiac safety profile of compounds. However, the relative inability to acquire abundant pure and mature cardiomyocytes still hinders these applications. Recently, it was reported that glucose-depleted culture medium supplemented with lactate can facilitate purification of hPSC-derived cardiomyocytes. Here, we report that fatty acid as a lactate replacement has not only a similar purification effect but also improves the electrophysiological characteristics of hPSC-derived cardiomyocytes. Glucose-depleted culture medium supplemented with fatty acid and 3,3’,5-Triiodo-L-thyronine (T3) was used during enrichment of hPSC-derived cardiomyocytes. Compared to untreated control cells, the treated cardiomyocytes exhibited enhanced action potential maximum upstroke velocity (as shown by a significant increase in dV/dtmax), action potential amplitude (APA), as well as action potential duration at 50% (APD50) and 90% (APD90) of repolarization. The treated cardiomyocytes displayed higher sensitivity to isoproterenol, more organized sarcomeric structures, and lower proliferative activity. Expression profiling showed that various ion channel and cardiac-specific genes were elevated as well. Our results suggest that the use of fatty acid and T3 can facilitate purification and maturation of hPSC-derived cardiomyocytes.